Predicting the sustainability of family business in the rice milling industry: A multiple case study - Rosid, Andiana; Sobirin, Achmad; Hendri, Nedi (Asian Management and Business Review, 2025)
The rice milling industry (RMI) is one of the oldest industries in the world and is dominated by small-scale family businesses. After decades, the RMI in Indonesia has experienced a cycle of stagnation and has struggled to develop due to various internal and external factors. This paper attempts to predict the sustainability of family businesses in the RMI. This study uses a multiple case study approach and involves 9 family businesses located in Central Lampung, Lampung Province, Indonesia. The nine family businesses are grouped into three categories: 3 small-scale rice mills (SRM), 3 medium-scale rice mills (MRM), and 3 large-scale rice mills (LRM). Data collection was conducted with in-depth interviews and supported by the McKinsey/General Electric (GE) matrix as an analytical tool to assess business strength and industry attractiveness. The results show that SRM has a low GE matrix value in terms of both its business strength and industry attractiveness. As a consequence, they have switched to other businesses and do not expect the next generation to continue the business. MRM generally has medium GE matrix values on both sides. They are trying to survive while waiting for the industry environment to become more conducive. Only LRM has a high value on both sides. They try to modernize the technology and involve the next generation to continue the business. The results of this study illustrate the possibility of a shift in the scale of RMI in the future, where SRM’s family business is expected to withdraw from the industry, and what remains are MRM and LRM.